Comparison of germination responses of Anigozanthos flavidus (Haemodoraceae), Gyrostemon racemiger and Gyrostemon ramulosus (Gyrostemonaceae) to smoke-water and the smoke-derived compounds karrikinolide (KAR1) and glyceronitrile - Downes, Katherine; Light, M.; Pošta, M.; Kohout, L.; van Staden, J. (Oxford University Press, 2012)
Background and Aims: A major germination-promoting chemical in smoke-water is 3-methyl-2H-furo[2,3-c]pyran-2-one (karrikinolide, KAR1). However, not all species that germinate in response to smoke-water are responsive to KAR1, such as Tersonia cyathiflora (Gyrostemonaceae). In this study, a test was made of whether two Gyrostemon species (Gyrostemonaceae) that have previously been shown to respond to smoke-water, respond to KAR1. If not, then the smoke-derived chemical that stimulates germination of these species is currently unknown. Recently, glyceronitrile was isolated from smoke-water and promoted the germination of certain Anigozanthos species (Haemodoraceae). Whether this chemical promotes Gyrostemon racemiger germination is also examined. Furthermore, an investigation was carried out into whether these species germinate in response to smoke-water derived from burning cellulose alone. Methods: Gyrostemon racemiger and G. ramulosus seeds were buried after collection and retrieved in autumn the following year when dormancy was alleviated and seeds had become responsive to smoke-water. Anigozanthos flavidus seeds were after-ripened at 35 °C to alleviate dormancy. Gyrostemon and Anigozanthos seeds were then tested with ‘Seed Starter’ smoke-water, KAR1, glyceronitrile and cellulose-derived smoke-water.Key Results: Although Gyrostemon racemiger, G. ramulosus and A. flavidus were all stimulated to germinate by ‘Seed Starter’ smoke-water, none of these species responded to KAR1. Gyrostemon racemiger germination was not promoted by glyceronitrile. This is in contrast to A. flavidus, where glyceronitrile, at concentrations of 1–500 µm, promoted germination, although seedling growth was inhibited at ≥400 µm. Maximum A. flavidus germination occurred at glyceronitrile concentrations of 25–300 µm. Some Gyrostemon germination was promoted by cellulose-derived smoke-water. Conclusions: KAR1 and glyceronitrile, chemicals in smoke-water that are known to stimulate germination in other species, did not promote the germination of G. racemiger. This suggests that other chemical(s) which promote germination are present in smoke, and may be derived from burning cellulose alone.